PENGARUH KUALITAS LAYANAN INTI DAN KUALITAS LAYANAN PERIPHERAL TERHADAP KEPUASAN PELANGGAN DI KZ ALLSHOP BENGKULU - Cahyono, Wahyu; Bustami, Taufik (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the effect of Core Service Quality, Peripheral Service Quality on KZ Allshop Bengkulu Customer Satisfaction. There are several factors that will be discussed in this study including, Core Service Quality, Peripheral Service Quality and Customer Satisfaction. This research uses quantitative research methods. The population in this study is all KZ Allshop Bengkulu customers. In this study using data collection methods by way of observation, interviews and distributing questionnaires or questionnaires. The data that has been collected is then processed using instrument tests, Respondent Response Analysis, Classical Assumptions Test, Multiple Linear Regression Analysis, Coefficient of Determination (R2) and also Hypothesis Testing. From the results of data management, it can be concluded that all independent variables, namely Core Service Quality and Pherieal Service Quality, partially or simultaneously have a significant effect on the dependent variable namely Customer Satisfaction.Keywords: Quality, Core Service, Peripheral Service, Customer Satisfaction. Keywords: Quality, Core Services, Peripheral Services, Customer Satisfaction